2012
DOI: 10.1177/2048872612455143
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion delay in patients treated with primary percutaneous coronary intervention: insight from a real world Danish ST-segment elevation myocardial infarction population in the era of telemedicine

Abstract: Background: Reperfusion delay in ST-segment elevation myocardial infarction (STEMI) predicts adverse outcome. We evaluated time from alarm call (system delay) and time from first medical contact (PCI-related delay), where fibrinolysis could be initiated, to balloon inflation in a pre-hospital organization with tele-transmitted electrocardiograms, field triage and direct transfer to a 24/7 primary percutaneous coronary intervention (PPCI) center. Methods and results:This was a single center cohort study with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 40 publications
2
26
0
3
Order By: Relevance
“…This difference may be due to geographical differences, but further studies are required to explain this difference. Notably, the system delay for patients living more than 100 km from the PCI centre in our study was comparable to the system delay achieved for patients living 65–100 km from the PCI centre in a previous Danish study,15 which highlights the optimal setup in the present study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This difference may be due to geographical differences, but further studies are required to explain this difference. Notably, the system delay for patients living more than 100 km from the PCI centre in our study was comparable to the system delay achieved for patients living 65–100 km from the PCI centre in a previous Danish study,15 which highlights the optimal setup in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Patients transported >11 km can bypass the city centre and save some transport time, and system delay may therefore be shorter for these patients. A recently published study15 using data from a prehospital setup that was nearly identical with the one used by us found a median system delay of 173 min in patients living >100 km from a PCI centre. We found a median system delay of 133 min in patients living >100 km from the PCI centre (table 3), which is considerably lower.…”
Section: Discussionmentioning
confidence: 68%
“…Also, the finding that 72% of patients are directly referred for primary PCI after prehospital diagnosis closely resembles the rate of 73% recently reported in a small single-centre study. 18 Remarkably, we found that distance travelled by EMS was not predictive of ischemic time in multivariable analysis. This suggests that, within our geographical context, distance travelled by EMS is of minor relevance for total ischemic time.…”
Section: Discussionmentioning
confidence: 71%
“…Several studies have clearly demonstrated how pre-hospital diagnosis and networking strongly reduce ischaemia time and increase the percentage of patients undergoing reperfusion within the golden hours [248,249]. The large STEMI campaign launched by the ''Stent for Life'' initiative (www.stentforlife.com) to support STEMI networks in Europe as well as in several other continents, together with public campaigns, will certainly contribute in coming years to significantly increase the proportion of patients presenting at first medical contact within the early phase (golden hours) of infarction and therefore highly suitable for a more aggressive pharmacoinvasive approach started in the ambulance, especially when long-distance transportation is needed.…”
Section: Upstream Therapymentioning
confidence: 99%